ADAPTIVE CRUISE CONTROL FOR AUTONOMOUS TRAM IMPLEMENTED ON HARDWARE IN THE LOOP SIMULATION - Syauqy, Abdurraafi'
ABSTRACT Adaptive Cruise Control for Autonomous Tram Implemented on Hardware In the Loop Simulation By Abdurraafi’ Syauqy NIM: 13218016 Bachelor’s Program in Electrical Engineering Trams are prone to collisions because they share the road with other vehicles and pedestrians. The tram's high mass makes it difficult for it to adjust its speed in response to its surroundings. The distance is too close for the tram to stop in time if a collision is imminent. Drivers who are not paying attention are sometimes a factor in tram accidents. As a result, Adaptive Cruise Control was proposed as a solution to this problem, so that the tram can more reliably regulate the appropriate speed while adapting to its environment and maintaining a safe distance from other objects in front of it. Adaptive Cruise Control has two control levels: High Level Control and Low Level Control. In High Level Control, Model Predictive Control will be implemented, which will determine the appropriate acceleration or deceleration based on the conditions around the tram to be used as the next reference speed. The advantage of this method is that it overcomes the passenger comfort constraint by not providing an acceleration or deceleration value that exceeds the comfortable limit. Low Level Control, which uses a PID control algorithm to determine the appropriate throttle to apply to the tram, will achieve the reference speed. Prior to implementing Adaptive Cruise Control on a real tram system, this algorithm will be tested on Hardware In the Loop Simulation, which is testing the algorithm on the same hardware as the one that will be implemented on the tram but in a simulation environment, to reduce the risk due to system imperfections. to see if a tram in a simulated environment controlled by the same hardware could maintain a safe distance without crossing the passenger comfort bat. The results of this test will serve as the foundation for future development of this algorithm on real trams. Keywords: adaptive, distance, speed, control, comfortable, throttle, tram.